Conditions of workers’ participation in the European context-works councils structures in the Central and Eastern Europe - Skorupińska, Katarzyna (Comparative Economic Research. Central and Eastern Europe, 2010)
The implementation of the 2002 Directive caused establishment of participation structures in coimtries of the Central and Eastern Europę following the pattern of works councils in Western Europę. The institiitions of workers participation have right to information and consultation but they do not possess the right to codetermination which for a long time has been granted to most works councils in the old EU Member States. Works councils in the new EU Member States have not been established on the road of organie development but they had to define their entitlements and evolve organizational structures themselves. In this article two major topics are discussed: types of employees' interests representation and dijferences in structures of works councils in coimtries of the Central and Eastern Europę. The main aim of the paper is to present the most important factors which affect the establishment and creation of such institiitions.